The Decent Work Questionnaire: Psychometric properties of the Italian version - Santos, Nuno Rebelo dos (2021)
Decent work is an integrative concept that may account for several labor-related issues. It represents the defence and promotion of human rights at work and business and the fulfilling and productive work maintained with social dialogue. Previous studies developed the Decent Work Questionnaire (Ferraro, Pais, dos Santos, et al., 2018) based on International Labor Organization propositions and workers' perceptions. The paper reports the adaptation and validation of its Italian version in a high-skilled workers sample (N = 1,465). Confirmatory factor analysis confirmed the original version's structural dimensions and good internal consistency reliability. Convergent and discriminant validity, tested using work engagement and personal burnout scales, were supported by the data. Therefore, the DWQ Italian version appears to yield reliable and valid data as a Decent Work measure in Italian workplaces.